Spatio-temporal variability of chlorophyll-a in response to coastal upwelling and mesoscale eddies in the South Eastern Arabian Sea. Issue 13 (3rd July 2021) - Shafeeque, Muhammad; Balchand, A. N.; Shah, Phiros; George, Grinson; B. R., Smitha; Varghese, Eldho; Joseph, Ajith K.; Sathyendranath, Shubha; Platt, Trevor
ABSTRACT: The influence of mesoscale dynamics on variability of phytoplankton biomass in terms of chlorophyll -a (chl -a ) concentration was studied in the coastal waters of the South Eastern Arabian Sea (SEAS) using long-term satellite data. Satellite-derived chl -a, sea level anomaly, sea surface temperature, and sea surface wind data for the period 1998–2016 were compiled from various sources and analysed to investigate the chl -a variability associated with coastal upwelling and mesoscale eddies. The Empirical Orthogonal Function and Morlet wavelet analyses were performed to estimate the quantitative variability and the result showed strong seasonal and interannual modulation in chl -a concentration and associated environmental variables. The Okubo–Weiss criterion was applied for the identification of mesoscale eddies. The results indicated the presence of cyclonic (cold core) eddies during the summer monsoon season (June–September). The wind-induced upwelling and the cyclonic eddies were most intense during the summer monsoon season, causing higher values of chl -a compared with other season. It is revealed that the variability of chl -a, which might be attributed to seasonal and interannual differences in the surface and sub-surface nutrients, is caused either by coastal upwelling or cyclonic eddies. In particular, the wind-induced upwelling strongly controls the spatial and temporal variability of chl -a compared with mesoscale eddies along the SEAS. The regression model we adopted points out the dominant role played by the wind and its forcing bring about variability in chl- a . The occurrence of extreme climatic events such as El Niño, La Niña and Indian Ocean Dipole (IOD) was noticed during the study period and particularly taken into account to understand the interannual fluctuations in chl- a and associated environmental variables. The relative variability in chl- a concentration was prominent during strong El Niño, La Niña, and IOD. We have attempted to determine the relationship between chl -a with coastal upwelling and mesoscale eddies, the overall importance of such physical forcings, and their influence on bio-production in the SEAS.